Drip Irrigation Performance Assessment In Latosol Soil Caisim (Brassica juncea L.) Cultivation - Hotlin Dermawati Apriani; Sumono Sumono; Sulastri Panggabean (Universitas Sumatera Utara, 2015)
Drip irrigation is needed in the efficient use of water for the plant and also attention is needed for its performance. The study was aimed to determine the performance of drip irrigation on Latosol soil with and without Caisim plants (Brassica juncea L.). Parameters measured were soil physical properties, evapotranspiration, field capacity, emission uniformity, drip irrigation efficiency, and Caisim (Brassica juncea L.) dry weight. The results showed that Latosol soil had clayey loam texture with a bulk density value of 1,05 g/cm3, particle density of 2,5 g/cm, porosity of 58,07% and a water content of 36,67% field capacity, evapotranspiration in the early phase was 1,11 mm/day, in the middle phase was 1,91 mm/day, and in the final phase was 1,18 mm/day, the average emission uniformity was 91,86%, the efficiency of use of irrigation in the final phase of plant growth was 100% on the ground with or without plants. Irrigation storage efficiency value at the end of the growth phase on soil with plants was 49,28% and was 15,42% on soil without plants, Caisim had an average dry weight of 1,65 grams and a water content of 87,66%. Keywords: caisim, drip irrigation, efficiency, latosol soil, performance